(untitled) (REMUNOM, 2025)
The transition from medical school to professional practice is marked by uncertainties regarding specialty choice, career perspectives, and labor market insertion. Given this scenario, an online educational event was held with the objective of promoting reflections on medical career paths and broadening students’ knowledge about professional opportunities. This article aims to describe the process of organizing and conducting the event, as well as to analyze its educational impacts and operational challenges. The activity was structured over two days and featured seven physician speakers who discussed topics related to medical residency, professional fields, medical marketing, and the ethical and bureaucratic aspects of medical practice. There was wide participation of students from different institutions across the country, demonstrating the potential of the virtual format for complementary medical education initiatives. The analysis highlights the importance of formative spaces that address professional identity construction and career guidance during undergraduate medical education, reinforcing the need to integrate these themes into the medical curriculum.